What can lead to late diagnosis of HIV in an illegal gold mining environment? A qualitative study at the French Guiana's border with Brazil. Issue 9 (5th September 2022) - Floersheim, Charlotte; Musso, Sandrine; Eubanks, August; Douine, Maylis; Spire, Bruno; Sagaon-Teyssier, Luis; Parriault, Marie Claire; Girard, Gabriel; Mosnier, Emilie
Abstract : Objective: The present study aimed to understand what factors can lead to late HIV diagnosis of illegal gold miners at French Guiana's border with Brazil. Design: An exploratory qualitative study with in-depth interviews and observations was conducted between November 2019 and February 2020. Setting: The study was conducted in the main medical healthcare service and two non-governmental organisation premises in the Oyapock border region, which is a supply area for illegal gold mining sites. Participants: Fifteen people living with HIV diagnosed with CD4 count <350 cells 10 6 /L were interviewed. Seven women and eight men participated; they were between 31 and 79 years old, and the median time since HIV diagnosis was 6 years. Eight had links to illegal gold mining. Findings: Three key themes for late HIV diagnosis emerged: (1) the presence of economic and political structural factors which constitute risks for this illegal activity, specifically the repression of gold mining sites by French Armed Forces and the distance from healthcare facilities; (2) representations of the body and health, related to the living conditions of this population; prioritisation of health emergencies and long-term self-medication; and (3) gender roles shaping masculinity and heterosexuality contributing to a perception of not being at risk of HIV and delaying testing. Conclusion: This study highlights structural, group-based and individual factors that reduce access to HIV testing and healthcare in general for a population of migrant workers in an illegal gold mining area. Faced with harsh living conditions and state repression, these workers develop a vision of health which prioritises the functionality of the body. Associated with gender roles which are partly shaped both by the mining activity and its geographical location, this vision can lead to late HIV diagnosis.